The Influence of Classroom Management on Students' Learning Motivation in the Department of Office Administration - Suprianto Suprianto; Emma Juwita Magdalena Sirait; Sitti Hardiyanti Arhas (Jurnal Office, 2021)
This study aims to determine the description of classroom management and the level of student learning motivation and the effect of Class Management on Student Learning Motivation in the Department of Office Administration at SMK Negeri 1 Watampone, Bone Regency. This study uses a quantitative study with a population of all students at SMK Negeri 1 Watampone totaling 384 students, with a sample of 40 students at an error rate of 10%. Data was collected by means of observation, questionnaires, and documentation. The data analysis technique used is a descriptive statistical analysis using the formula of the mean (mean), standard deviation, and inferential statistical analysis using simple regression for hypothesis testing. The results showed that classroom management at the Office Administration Department of SMK Negeri 1 Watampone was classified as good, this was supported by the power approach, freedom approach, role balance approach, teaching approach, emotional and social atmosphere approach, and a combination approach. Meanwhile, the learning motivation of students in the Office Administration Department at SMK Negeri 1 Watampone is classified as high, this is supported by intrinsic motivation and extrinsic motivation. In addition, the results of the study indicate that there is a significant positive effect of classroom management on student motivation in the Office Administration Department at SMK Negeri 1 Watampone, Bone Regency. This can be seen from the results of data analysis carried out, obtained the level of influence of classroom management on learning motivation is classified in the low category, this is caused by other factors not examined in this study.